Preliminary Research on the Health-Promoting Value of Honeydew Honey Enriched with Bee Bread - Alicja Sęk; Sara Olszak; Katarzyna Jaśkiewicz; Teresa Szczęsna (Molecules)
Since the imbalance between free radicals and antioxidants in the body plays a significant role in the physiology of common, often dangerous diseases, an emphasis is placed on enriching the daily diet with compounds characterized by antioxidant activity. Good sources of natural antioxidants are bee products such as honey, bee pollen, bee bread and propolis, and the best path for introducing the latter products into the diet is mixing them with honey. However, the characteristics of bee product mixtures are not yet fully understood. Therefore, the aim of this study is to verify the health-promoting properties of a mixture of honeydew honey and multifloral bee bread. The profile of phenolic compounds, radical scavenging activity, total phenolic content, diastase number, and also proline and HMF content were determined. The obtained results indicated the improved health-promoting value of this mixture, as increases in radical scavenging activity (from 82.7 to 88.4%), in the total content of phenolic compounds (from 74.6 to 118.8 mg·100 g−1), and also in the proline content (from 64.0 to 95.5 mg·100 g−1) and diastase activity (from 22.6 to 38.8 Schade units) were observed when 5% of bee bread (w/w) was added. Moreover, the bee bread addition provided two important flavonoids to the honeydew honey, i.e., rutin and kaempferol.